Human ileal organoid model recapitulates clinical incidence of diarrhea associated with small molecule drugs. (October 2020) - Belair, David G.; Visconti, Richard J.; Hong, Miyoun; Marella, Mathieu; Peters, Matthew F.; Scott, Clay W.; Kolaja, Kyle L.
Abstract: Drug-induced gastrointestinal toxicity (GIT) is a common treatment-emergent adverse event that can negatively impact dosing, thereby limiting efficacy and treatment options for patients. An in vitro assay of GIT is needed to address patient variability, mimic the microphysiology of the gut, and accurately predict drug-induced GIT. Primary human ileal organoids (termed 'enteroids') have proven useful for stimulating intestinal stem cell proliferation and differentiation to multiple cell types present in the gut epithelium. Enteroids have enabled characterization of gut biology and the signaling involved in the pathogenesis of disease. Here, enteroids were differentiated from four healthy human donors and assessed for culture duration-dependent differentiation status by immunostaining for gut epithelial markers lysozyme, chromogranin A, mucin, and sucrase isomaltase. Differentiated enteroids were evaluated with a reference set of 31 drugs exhibiting varying degrees of clinical incidence of diarrhea, a common manifestation of GIT that can be caused by drug-induced thinning of the gut epithelium. An assay examining enteroid viability in response to drug treatment demonstrated 90% accuracy for recapitulating the incidence of drug-induced diarrhea. The human enteroid viability assay developed here presents a promising in vitro model for evaluating drug-induced diarrhea. Highlights: Drug-induced gastrointestinal toxicity (GIT) is a common treatment-emergent adverse event in clinical trials. Rodent models fail to predict drug-induced GIT. Organoids derived from healthy human small intestinal tissue and differentiated for 7–10 days express the four epithelial subtypes present in the small intestine. An in vitro human gut organoid model was 90% predictive of drug-induced GIT across a 31-drug reference set.